Effectiveness of Vermicomposting in Management of Organic Wastes using Eisenia foetida and Perionyx favatus in Central Zoo Jawalakhel, Nepal - Dhimal, Meghnath; Gautam, Ishan; Tuladhar, Reshma (Journal of Natural History Museum, 2015)
Management of Zoo wastes has been increasing problem in urban areas. The major part of the Zoo waste is organic material contributing from animal dungs, garbage and litter which can be converted into fertile compost. We used the vermicomposting techniques for converting the elephant dung, rhino dung, garbage and litter into compost in relatively short time compared to traditional method of composting. The physico-chemical and microbiological parameters of thus prepared compost were tested adopting standard scientific methods. The analysis showed that pH, organic matter content, moisture content, nitrogen, phosphorous, potassium and (Carbon:Nitrogen) C: N value are appropriate for utilizing in the farming. Thus vermicomposting is one of the viable options for converting huge amount of organic waste into high quality compost effectively. J. Nat. Hist. Mus. Vol. 27, 2013: 92-106